KATEKIS DAN PASTORAL POLITIK - Inosentius Mansur (STIPAS St. Sirilus Ruteng, 2014)
The notion of politic from Fr. Ino takes account not only of the personal and inter-personal aspect of Christian faith buat also ofits public and “political